Regenerating the NC code in order to improve the surface quality - Dragan Lazarević; Bogdan Nedić; Vlatko Marušić; Milan Mišić; Živče Šarkoćević (Tehnički Vjesnik, 2017)
The paper presents the research results of the impact of variable machining parameters: feed and spindle speed on surface roughness of Aluminium alloy 6005-T6, at CNC in the up and down milling with tools of different dimensions and different materials (Ø6 HSS, Ø6 VHM and Ø10 VHM). The properties and classification of Aluminium alloys are cited. The definition of surface roughness at end milling is given and parameters that affect it are specified. It was concluded that the feed is the parameter that has the most influence on surface roughens, while the lowest roughness is achieved by up milling. Correlation equations have provided good prediction of surface roughness in the case of machining of VHM by cutter Ø10. The results of the experiment will serve as an input into the model for control of input parameters of the machining process by regeneration of NC code for the purpose of quality improvement of machined surface.